Untangling the quality of governance from the level of income: Are Sub-Saharan African countries governed well? - Erich Gundlach; Susanne Hartmann (Kiel Institute for World Economics (IfW), 2005)
We consider whether Sub-Saharan African (SSA) countries are mainly poor because they are governed worse than other countries, as suggested by recent studies on the supremacy of institutions. Our empirical results show that the supremacy of institutions does not hold. SSA countries appear to face very specific development problems. Given their geographic and economic constraints, we conclude that SSA countries are on average not governed worse than other comparable countries. Our finding supports the basic argument of a recent UN report (UN Millennium Project 2005). However, we find that the UN report is based on empirical evidence that appears to imply the supremacy of institutions.
Keywords: O1; O4; 330; Institutions; Disease ecology; Sub-Saharan Africa; Development; Sozialprodukt; Institutionalismus; Schätzung; Zentralafrika